50 greats for the Piano (Yamaha, 2012)
This book is worth it's weight in gold if you are the owner of a Yamaha digital piano. Even though the book is 10 years old, all the 50 songs are preset in the keyboard. And with a Yamaha you can slow the song down, play just the left or right hand by itself. Great for learning. The only drawback would be the fact that the book does not stay flat on the music stand, it is not spiral bound - I ended up taking photocopies of the songs that interested me.